Dayah-Based Education Management in Shaping Muslim Personality at SMP Darul Madaris - Miftahudin (Wasatha: Jurnal Studi Islam dan Humaniora, 2024)
This research was raised based on the importance of manajement based on Dayah in the midle of modern era. This modern era often has a negative impact and changes the behavior of students to become more secular and do not have good morals. So, from this background, the researcher is interested in examining the importance of Dayah-based education management in shaping the Muslim personality of students at SMP Darul Madaris so that the young generation can have a personality that is in accordance with Islamic law and based on the Qur'an. However, there are supporting and inhibiting factors in carrying out the education management process. This study uses descriptive qualitative methods by describing phenomena that occur in the field and analyzed using existing theories. The results of the study show that the management of Islamic boarding school-based education at Darul Madaris Middle School is very good so that it can shape the Muslim personality of students. As well as in its implementation there are supporting and inhibiting factors from the internal and external sides.